Photocurrent Generation of TiO2 and CuO Doped MWCNT Buckypaper - Miao1, Hsin-Yuan; Liu1, Jih-Hsin; Saravanan3, L.; Wang2, Li-Chih; Waychen1, Tu (Asian Journal of Chemistry, 2013)
In this work, we report the TiO2 and CuO dispersed multi-walled carbon nanotube buckypaper are photo-electro active and generate photocurrent upon visible light excitation without any bias voltage. The size of the nanoparticles dispersed in MWCNT networks was 5.83 and 6.85 nm for TiO2 and CuO respectively. The photocurrent value of TiO2-BP (6 μA) and CuO-BP (7 μA) was obtained respectively by the time dependent ON-OFF illumination of visible light. The samples show the stable value of photo voltage without any fluctuation for long time duration upon irradiation. We also measured the carrier mobility, concentration and hall coefficient by the Hall measurements. It can be considered that upon doping TiO2 and CuO, the observed photoelectric effect was due to electron transfer occurred between MWCNT and metal oxide.